Sistem Deteksi Lama Waktu Penyimpanan Daging Ayam Berdasarkan Warna Dan Kadar Amonia Berbasis Sensor TCS3200 dan MQ135 Dengan Metode Jaringan Syaraf Tiruan - M. Adib Fauzi Rahmana; Dahnial Syauqy; Tibyani Tibyani (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2019)
The length of time for storing chicken meat is the important factor that is related to the freshness and quality of chicken meat whether or not the meat is suitable for consumption. It is very important in determining the feasibility of chicken meat for consumption. In this research, it is designed a system that can be used fastly, accurately, and non-destructive. This system is implemented into an Arduino microcontroller by using gas sensors and color sensors as a measurement tool for determining chicken meat based on length of time storage. The process of inputting data is gained by data acquisition with two sensors, there are MQ135 gas sensor and TCS3200 color sensor which is able to read parameters in the form of ammonia levels and RGB colors. For the classification process, supervised learning algorithms are used from artificial neural networks that are able to recognize and group data based on predetermined targets at the beginning. There are 3 types of chicken meat based on the length of time storage. First, meat of chicken that are only slaughtered up to 12 hours long storage time. Second, it is stored longer than 12 hours up to 24 hours.The last, it has been stored for more than 24 hours. This research gave accuracy system of 86.7% in deciding time of period chicken meat time storage, by average computational time needed for 3.2 seconds.